Identification of fuzzy boundaries of cutter power using control chart method - Andrey K. Tugengold; Andrey I. Izyumov; DmitryY. . Terekhov (Advanced Engineering Research, 2016)
The body of knowledge of the intelligent control system e-MindMachine of the multi-operation machine contains each tool condition data including its remaining life time. This is required to obtain conclusions on the possibility of the planned machining pass, the wear size value, the necessity to change cutting conditions during the operation in the fuzzy boundary strip area, etc. In addition to the previously described methods of assessing the initial and final values of the boundary strip time as an uncertainty state area, a visual method using a modification of Shewhart control charts is offered. The adaptive control charts allow tracking the tool wear progress warning of deviations from the requirements to the process. A program sheet with the appropriate control charts and examples of their usage for the assessing the tool state and forecasting the boundary strip parameters is presented. The dependences of estimations of the expectation of the wear size and scattering within the linear tool wear zone, appropriate velocity functions and a posteriori values for the future operation in the boundary strip area are described. On this basis, the timing estimation of the boundary strip head and end is predicted. The processing of the statistical control charts is performed by the MATLABStatisticstoolbox application package.